(3cJGH aj GdcjejGA heG jJYdb HgGs
(3ChdgG (B:s
(3GdMeO ddg LGeY Ted GdGMHGH hHYO agPg eLehYI dWjaI haQGFO XQjaI LeYJgG ef cJH YOjOI hCSYGQ eajOI ChQOJ aQGFO YQSgG aj bhGdH GdEYLGH s
(3BNQgG (B:s
(3BNQ GdehLhO Hg GdHGH GdJGSY aj cTa GSQGQge aj hgf GdGLQ GYde Cf gPG GdOge GdeTGQ Zdjg dg aYd YXje aj GdGNdGW hGdHQhOGJ s
(3HgG fXGe GdJYbjHIs
(3hHChQGbI GVWQGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs